Job Loss in the Great Recession and its Aftermath: U.S. Evidence from the Displaced Workers Survey - Henry S Farber (Institute for the Study of Labor (IZA), 2015)
The Great Recession from December 2007 to June 2009 is associated with a dramatic weakening of the labor market from which, by some measures, it has not completely recovered. I use data from the Displaced Workers Survey (DWS) from 1984-2014 to investigate the incidence and consequences of job loss from 1981-2013. In particular, the 2010, 2012, and 2014 DWSs provide a window through which to examine the experience of job losers in the Great Recession and its aftermath and to compare their experience to that of earlier job losers. These data show a record high rate of job loss in the Great Recession, with almost one in six workers reporting having lost a job in the 2007-2009 period, that has not yet returned to pre-recession levels. The employment consequences of job loss are also very serious during this period with very low rates of reemployment and difficulty finding full-time employment. The reduction in weekly earnings for those job losers during the 2007-2013 period who were able to find new employment are not unusually large by historical standards.
Keywords: J63; 330; job loss; unemployment; wage loss